Lifespan neuroimaging of the 5xFAD mouse model of Alzheimer's disease: Evolution of metabolic and vascular perturbations: Neuroimaging / animal imaging. (7th December 2020) - Szu, Jenny; Jullienne, Amandine; Obenaus, Andre; Territo, Paul R; Consortium, MODEL‐AD
Abstract: Background: The Model Organism Development and Evaluation for Late‐Onset Alzheimer's Disease (MODEL‐AD) consortium seeks to develop the next generation of Alzheimer's disease models guided by human data. As new mice models become available, they are extensively phenotyped and compared to existing models, such as the 5xFAD. The 5xFAD models familial AD onset, which results in amyloid β (Aβ) deposition and cognitive decrements early in life; however, no studies have comprehensively phenotyped the vascular and metabolic aspects of this mouse over its lifespan (∼15mo). Here we report lifespan perturbations in male and female 5xFAD mice compared to healthy aging C57BL/6J (WT) mice using multi‐modal neuroimaging with assessment of vascular networks. Method: Age (4, 8, 12mo) and sex‐matched 5xFAD and healthy aging WT (C57BL/6J) mice underwent ex vivo MRI and in vivo PET evaluation for regional brain volumes (T2‐weighted imaging), Aβ load (susceptibility weighted imaging and 18F‐AV45 PET) and brain metabolism (18F‐FDG PET). After neuroimaging, selected mice underwent novel vessel painting (VP) to label whole brain vascular networks. Histology and immunohistochemical analyses verified neuroimaging findings. Result: Whole brain volumes were significantly decreased (∼6%) in 8mo female 5xFAD compared to WT, as were hippocampal volumes in both sexes. SWI and AV45‐PET were able to detect elevated Aβ plaques with age in 8‐12mo old 5xFAD mice when compared to WT. 18F‐FDG showed a reduction in glycolysis with age when compared to WT. Whole brain vascular networks in 8mo 5xFAD mice had vessel numbers and complexity compared to 4mo 5xFAD, with males having larger reductions than females. The middle cerebral artery vessel density in 5xFAD was also decreased. Immunohistochemistry confirmed Aβ deposition and microglia activation with genotype and age. Conclusion: This is the first report of vascular and metabolic disturbances during the lifespan in the 5xFAD model of AD. Our findings suggest that vascular and metabolic ageing are correlated to temporal cumulative Aβ deposition. Early decrements in vascularity in the 5xFAD may precede the development of pathology. Further, the 5XFAD mice exhibit age and region‐specific neuroimaging alterations coincident with metabolic disturbances.